2012
DOI: 10.1002/ps.2278
|View full text |Cite
|
Sign up to set email alerts
|

Baseline susceptibility of a wild strain of Phlebotomus papatasi (Diptera: Psychodidae) to DDT and pyrethroids in an endemic focus of zoonotic cutaneous leishmaniasis in Iran

Abstract: The results of this study provide a guideline for implementation of different vector control measures. Furthermore, guidelines are needed for monitoring and evaluation of insecticide susceptibility tests against sand flies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Similar results have been found in insecticide-susceptible Italian P. perniciosus and P. papatasi, where the LT 50 's and LT 90 's for DDT were longer compared with permethrin and lambdacyhalothrin (Maroli et al 2002). Also, Saeidi et al (2012) found both insecticide-susceptible male and female P. papatasi to have much longer LT 50 's and LT 90 's to DDT than to permethrin, deltamethrin, cyfluthrin, and lambda-cyhalothrin.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Similar results have been found in insecticide-susceptible Italian P. perniciosus and P. papatasi, where the LT 50 's and LT 90 's for DDT were longer compared with permethrin and lambdacyhalothrin (Maroli et al 2002). Also, Saeidi et al (2012) found both insecticide-susceptible male and female P. papatasi to have much longer LT 50 's and LT 90 's to DDT than to permethrin, deltamethrin, cyfluthrin, and lambda-cyhalothrin.…”
Section: Discussionmentioning
confidence: 91%
“…For many years, DDT has been used worldwide to control sand flies by direct intervention or inadvertently as a collateral benefit of antimalaria campaigns (Kaul et al 1994, Alexander and Maroli 2003, Surendran et al 2005, Kishore et al 2006, Dinesh et al 2010, Afshar et al 2011, Faraj et al 2012, Saeidi et al 2012). Our results suggest that laboratory colonies of insecticide-susceptible sand flies are not very susceptible to DDT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many years, DDT has been used worldwide for controlling sand flies through direct intervention or inadvertently as a collateral benefit of anti-malaria campaigns (24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%